Spatial–temporal precipitation analysis in the area between Scrivia T. and Nure T. (Northern Italy) - Maggi, I; Ottone, C (Quaternary international, 2003)
Monthly and annual precipitation data (1921–90) from 99 rain gauges, distributed over the study area, were used to set up a framework of the total precipitation and to calculate the index of pluviovariability spatial–temporal distribution. The index of pluviovariability is indicative of the erosional potential of rainfall. The results show that, among the catchment basins considered, the Scrivia and Trebbia basins are the most rainy ones, with the highest pluviovariability class. Both parameters are subject to marked fluctuations. Through spectral analysis, the series have been subdivided into cycles. It was thus possible to identify a main 23.3-year cycle which can explain the variability of these series.